The Influence of Deep Learning With Spedomatik Media on Enhancing Collaborative and Critical Thingking Skills of Elementary School Students - Aprilia Nur Widyanti; Achmad Buchori; Ida Dwijayanti (FKIP - Universitas Riau, 2026)
This study investigates the effect of applying Deep Learning assisted by Spedomatik Media on improving collaborative skills and critical thinking among elementary school students. The research employed a quasi-experimental design with a one-group pretest-posttest approach. The sample consisted of 25 second-grade students from SDN 1 Sumberagung. Data were collected using pretests, posttests, observational checklists, and collaboration skills questionnaires. The results showed significant improvements in both collaborative skills and critical thinking after the intervention. The classical learning completeness increased from 0% to 80%, indicating the effectiveness of Deep Learning in enhancing student engagement and collaboration. The regression analysis indicated that Deep Learning contributed significantly to the improvement of both skills, with a 49.9% increase in collaborative skills and a 60.4% increase in critical thinking skills. The Manova test further confirmed the simultaneous effect of Deep Learning on both skills. These findings suggest that the integration of Spedomatik Media into Deep Learning strategies fosters a more interactive and effective learning environment, thereby enhancing students' ability to collaborate and think critically. The study highlights the potential of this approach for future educational practices in elementary schools.